La mise en scène des émotions dans le direct d’une chaîne tout info : le cas des attentats de Paris du 13 novembre 2015 - Pitoizet, Alice; Grossmann, Francis (Studia Romanica Posnaniensia, 2017)
Journalists play a crucial role in the reporting of events, especially in tragic circumstances, such as terrorist attacks. An all-news network must maintain a dramatic tension throughout the events, sometimes for long hours, although the reporters dispatched to the site are not always able to provide new elements. On the basis of the partial information transmitted from various sources, the on-site journalists have to develop a coherent story that captures the audience’s attention. This explains why the staging of the information is not only based on the emotions of the witnesses and on-site reporters, but also on narrative stereotypes or social scripts, leading to a form of fictionalization. Our study, which uses the methods of discourse analysis, takes into account the emotional lexicon and the way in which the interaction between the various protagonists of the journalistic discourse shapes the televisual macronarrative. It is based on a transcribed corpus of two hours of live news broadcast by BFM, a French news channel, during the attacks that took place in Paris on November 13, 2015.